Scapula manipulation on frozen shoulder condition: a case study - Ayuni Ashrifah; Suryo Saputra Perdana; Kingkinnarti (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Frozen shoulder or adhesive capsulitis is a stiffness in the shoulder joint, namely the thickening of the shoulder joint capsule tissue, resulting in pain and limited shoulder joint movement. In Indonesia, 2-11% of frozen shoulder sufferers have diabetes. Complaints in the shoulder also often accompany human movement activities due to gaps in body functions, including a frozen shoulder. Case description: This was a case study of a patient aged 56 years with a diagnosis of frozen shoulder; this case was taken at Dr. Harjono Ponorogo Hospital, held from March 3, 2023, to March 23, 2023. The physiotherapy problems encountered in this case included pain, limited joint motion, weakness in muscle strength, and limited functional activity. Conclusion: At three meetings, the patient was given intervention in the form of scapular mobilization, which decreased pain and increased the range of motion on the shoulder. A decrease in limitations can also be seen from the measurements used by the shoulder pain and disability index (SPADI), but in the SPADI assessment, there were no significant changes.